How can stimuli and emotions help increase brand advocacy - Loureiro, S. M. C.; Bilro, R. (21st World Marketing Congress of the Academy of Marketing Science, 2018)
The current study aims to explore if Information/Content, Interactive Features, and Design-Visual appeal influences consumers emotional states of Pleasure, Arousal, and Dominance (PDA), leading to brand advocacy as an outcome. Therefore, our goal is to understand which stimuli of experience exercises more effect on the three emotional states (PDA) and which of these three better influence Brand Advocacy. Data from 183 users of CGM were analysed through structural equation modelling (SmarthPLS2.0) and the findings show that all the aforementioned stimuli influence online PDA. Findings also suggest that all PDA dimensions influence Brand Advocacy.